Perbandingan Hasil Belajar Siswa Yang Menggunakan Model Pembelajaran Think Talk Write dan Think Pair Share - Fadila, Ila Putri; Imron, Ali; Susanto, Henry (FKIP UNIVERSITAS LAMPUNG, 2020)
This study aims to determine the differences in students' learning outcomes by comparing the Think Talk Write learning model and Think Pair Share learning model in History subject for students in Grade X TKJ of Public Vocational High School 1 Tanjungsari. The research method used in this study is Quasi Experimental with Nonequivalent Control Group Design. The sampling technique in this study was conducted through purposive sampling. The results showed that the students' learning outcomes from the Think Talk Write learning model were higher than those who applied the Think Pair Share learning model. This is indicated by the posttest hypothesis test using t-test. It can be concluded that there are differences in students' learning outcomes in History subject between the Think Talk Write learning model and the Think Pair Share learning model.Penelitian ini bertujuan untuk mengetahui adanya perbedaan hasil belajar siswa dengan membandingkan penggunaan model pembelajaran Think Talk Write dan model pembelajaran Think Pair Share pada mata pelajaran Sejarah kelas X TKJ di SMKN 1 Tanjungsari. Metode yang digunakan dakam peneltian ini adalah Quasi Experimental dan desain yang dipilih adalah Nonequivalent Control Grub Design. Teknik penentuan sampel pada penelitian ini menggunakan Purposive Sampling. Hasil penelitian menunjukan bahwa hasil belajar siswa yang menggunakan model pembelajaran Think Talk Write lebih tinggi dibanding dengan siswa yang menggunakan model pembelajaran Think Pair Share. Hal ini ditunjukan dengan uji hipotesis posttest menggunakana uji t. Bahwa ada perbedaan hasil belajar siswa pada mata pelajaran sejarah, antara penerapan model pembelajaran Think Talk Write dengan model pembelajaran Think Pair Share.Kata kunci: hasil belajar, model pembelajaran think talk write, model pembelajaran think pair share